Effects of tannins and saponins contained in foliage of Gliricidia sepium and pods of Enterolobium cyclocarpum on fermentation, methane emissions and rumen microbial population in crossbred heifers - Molina Botero, Isabel Cristina; Arroyave-Jaramillo, Julian; Valencia Salazar, Sara Stephanie; Barahona Rosales, Rolando; Aguilar-Pérez, Carlos Fernando; Ayala Burgos, Armín; Arango, Jacobo; Ku-Vera, Juan Carlos (Elsevier, 2019)
Incorporation of foliage and pods of tropical legumes in ruminant rations is an alternative to mitigate enteric methane emissions. The objective of this research was to evaluate the effect of adding increasing levels of ground pods of Enterolobium cyclocarpum (Jacq.) Griseb. mixed with foliage of Gliricidia sepium (Jacq.) Steud. on emissions of ruminal methane (CH4), volatile fatty acid proportions, rumen pH and microbial population in cattle. Four heifers (218 ± 18 kg LW) were fed (13 days) 0, 15, 30, and 45% of pods of E. cyclocarpum mixed with foliage of G. sepium, which were supplemented to a basal ration of Brachiaria brizantha (Hochst. ex A. Rich.) Stapf. Data were analyzed as a 4 × 4 Latin square. After three days of CH4 measurements in open-circuit respiration chambers, rumen fluid was collected to determine volatile fatty acid (VFA) molar proportions and quantify the microbial population. Samples of ration ingredients, refusals and feces were collected to evaluate nutrient composition. Foliage and pods of legumes provided crude protein (CP), condensed tannins (CT) and saponins, while grass was characterized by higher concentrations of neutral detergent fiber (NDF). Dry matter intake (DMI) was 5.35 kg/day on average (P = 0.272). Apparent fiber digestibility was reduced (81 g/kg) and digestible CP intake (13 g/kg) increased when E. cyclocarpum mixed with G. sepium in rations were given (P < 0.05). Incorporation of legume foliage and pods had a linear effect on molar proportions of butyric acid and acetic to propionic acid ratio (P < 0.05). Methane production, expressed on basis to digestible dry matter intake (DDMI), ranged between 43.22 and 49.94 g/kg DDMI (P = 0.131) and when CH4 was related to digestible CP (347 vs. 413 g CH4 /kg DCP) or annual weight gains (0.30 vs. 0.38 kg CH4/kg weight gain, P < 0.001) there were differences between the E. cyclocarpum mixed with G. sepium rations compared to the control treatment, respectively. Rumen population of total bacteria, methanogenic archaea, and total protozoa was not affected by the increasing levels of condensed tannins and saponins in rations (P > 0.05). Substitution of 15 and 30% of pods of E. cyclocarpum mixed with foliage of G. sepium in the ration, decreases annual methane emissions per unit product, without affecting dry matter intake or rumen microbial population, on the contrary, digestible CP intake and animal productivity increased due to supply of CP, CT and saponins.